Work, Professional Development And Teaching Commitment: Deconstructing Meanings. - Rivas-Flores, José Ignacio; Leite-Méndez, Analía Elizabeth; Cortés-González, Pablo; Medel Navarro, Ana Belén (My University, 2016)
The paper we present is part of the research project "The professional identity of teacher studies", that we are development for last 3 years. The third phase of this research put the focus on the experience of job placement of novel teachers, graduated no more than 5 years. We work with focal groups and professional experience and teacher education accounts of teachers implied in this research. Also, for any teachers, we do biographical interviews to deepen on processes of construction of professional identity. In this paper we present the Ana Belen History, a female teacher of pre-school education with an experience of 4 years in school, working in a urban school with students in risk of exclusion. This school have a educative project, commitment with the neighbourhood, joint with the community and other social groups. Ana Belen story, from professional perspective, is linked with the social politic and educational commitment of this school. Our interest is focused in the comprehension of professional identity that Ana Belen has gone forging along her personal story and how her education and job placement has contributed for it. Also we are interested in knowing how early professional experiences have influenced in her professional development as teacher. Specifically we ask ourselves about what influence have for her professional identity, that her career starts in this particular school. In consequence, this paper leads us to question the current teacher education model. In particular we are interested on the kind of professional experience that have place and, so, the kinds of commitments that enables. We understand that frameworks in which professional education and experience have place are relevant to enable more or less transformer understandings about teaching. From conceptual perspective this paper adopts a socio-critical point of view (Gergen, 1985; Kincheloe, 2001; Wenger, 1988, etc.). We understand that teaching has to be analysing according work contexts and personal stories of teachers, because we face processes historical and collective building. Teaching is the result of action of their actors, over time, and in specific stage. So, with this research we intend to break with the old gap between pre and in-service education. We think that both of them are part of the same process and are formed according similar logical; although scenes change. We understand that they are part of a continuous process in which is giving sense to different and complex settings where teaching profession is built, but they are not differenced and independent stages. The teacher work, so, is subject to particular conditions, generated from such different fields as institutional, corporative, cultural, social, political, moral, etc. It displays a kaleidoscopic view on space, time, context, ... These are the axis in which the teaching is formed, from the complexity and heterogeneity. How this complexity is articulated results in different ways to face the teacher work, according different personal and professional stories. The teacher acts with subjects in instituted contexts from relationships he has with them, which gives a situated and contingent character. But, these contexts are strongly structured and ruled according centralized and generalized positions; which is, at the very least, paradoxical. Possibly, from our point of view, same of the crisis of teaching have to explain from this paradoxical perspective and the conflict, which characterize this job (Rivas, Leite y Cortés, 2011)
Keywords: Profesores - Formación profesional; Educación infantil; Educación infantil; Identidad profesional; Historia de vida; Profesorado novel